A dynamic method for feeder reconfiguration and capacitor switching in smart distribution systems. (February 2017) - Ameli, Amir; Ahmadifar, Amir; Shariatkhah, Mohammad-Hossein; Vakilian, Mehdi; Haghifam, Mahmoud-Reza
Highlights: Minimizing total cost using reconfiguration and capacitor banks switching considering DGs. Dynamic scheduling of reconfiguration and capacitor banks switches for a period. Stochastic Calculations due to the variant output generation of the DG. Thorough cost func. including transformer loss of life, switching and other costs. Abstract: In distribution systems, feeder reconfiguration (FR) can lead to loss reduction, reliability improvement and some other economic savings. These advantages can be intensified by proper control and switching of Capacitor Banks (CBs). In this paper, using Ant Colony Optimization (ACO) technique, a novel method is proposed for simultaneous dynamic scheduling of FR and CB switching in the presence of DG units having uncertain and variant generations over time. This method is applicable to both smart and classic distribution systems. While for the latter, state estimation method should be used to estimate the loads at different buses by employing a limited number of measurements. The objective of this method is to minimize the total operational cost of the grid, including the cost of power purchase from the sub-transmission substation, cost of customer interruption penalties, Transformers Loss of Life (TLoL) expenses, and the switching costs (CBs and disconnecting switches). To perform this study, the planning period is divided into several intervals for each of them the network topology and CBs reactive power are determined to satisfy the objective function. Additionally, due to the curse of dimensionality, a Case Reduction Technique (CRT) is proposed in order to decrease the computational burden of the proposed method. Finally, the efficiency of the proposed method is verified through its application on the IEEE 118-bus distribution test system, and evaluating its economic and operational characteristics.